Projecto de Habitação Plurifamiliar no lugar de Canidelo. Identidade do lugar, condicionantes locais e necessidades contemporâneas do habitar - Samuel Martins Carreira (2022)
The present dissertation presents an architectural design exercise for a multi-family housing building located in a specific plot of land in the parish of Canidelo, Vila Nova de Gaia. Considering that this is a project commissioned from a specific promoter, with the practical possibility of construction in the near future, the project will serve as a basis for an eventual execution project; therefore, we aim to be as realistic and detailed as possible. In the context of the dissertation, we tried to make evident conditioning factors, pre-existing conditions, references, and project influences, as well as the main guiding principles of the proposal. In this sense, the aim is to demonstrate how the design method allows the approach to material and constructive reality, taking advantage of analogical and phenomenological interpretation of the symbologies and elements of local contexts. In this way, the relationship between man and the environment is valued through building design that gathers the necessary functions for living and relates its material side with the immaterial aspects of place and local culture. These architectural options are supported by the study and characterization of the surrounding preexistence and by considering the ideas of architects who express a critical and experimental vision regarding the environment's design relating to landscape and nature. The aim is to design residential architecture inspired by the permanent identity of the site and its urban context, considering the legal constraints imposed as part of the equation but incorporating equally an essential and symbolic expression associated with the place, which privileges the current needs of the inhabitant.